PENINGKATAN KEMAMPUAN KADER MEMANTAU PERTUMBUHAN BALITA DI POSYANDU - Fathurrahman Fathurrahman; Magdalena Magdalena; Nurhamidi Nurhamidi (Universitas Pahlawan Tuanku Tambusai, 2023)
There is still a shortage of active posyandu cadres in Martapura Barat District. Some cadres were recruited to replace cadres who had dropped out and had never been trained. Many Posyandu cadres have difficulty measuring toddlers’s height and weighing correctly. The purpose of this activity is to improve the ability of cadres to monitor the growth of toddlers in posyandu. The target of the activity was 43 posyandu cadres in Martapura Barat District. The activities were divided into two stages, namely training for cadres in class in the form of theory and practice for two days, and the second stage was field practice as well as fostering posyadu activitie. Material training is theory and practice of weighing, measuring height and length, filling in KMS, and counseling on nutrition. As a result of the activity, training has been carried out to improve the ability of cadres in monitoring growth. The activity was carried out at the Sungai Batang Ilir Village Hall. Weighing practices are carried out according to posyandu opening days. From the results of the activity, there was an increase in the knowledge and skills of cadres in carrying out the process of weighing weight and measuring TB as well as filling in the KMS. Skills of cadres in nutrition counseling at table 4 need to be improved and further coaching by related parties. Suggestions, it is necessary to periodically coach and refresh cadres by related parties, procure standard anthropometric tools, and increase the ability of cadres to provide counseling and nutrition counseling. Keywords: Ability of cadres, monitoring, growth of toddlers